Scale Invariant Disordered Nanotopography Promotes Hippocampal Neuron Development and Maturation with Involvement of Mechanotransductive Pathways - Schulte, Carsten; Ripamonti, Maddalena; Maffioli, Elisa; Cappelluti, Martino A.; Nonnis, Simona; Puricelli, Luca; Lamanna, Jacopo; Piazzoni, Claudio; Podestà, Alessandro; Lenardi, Cristina; Tedeschi, Gabriella; Malgaroli, Antonio; et al. (Frontiers in Cellular Neuroscience, 2016)
The identification of biomaterials which promote neuronal maturation up to the generation of integrated neural circuits is fundamental for modern neuroscience. The development of neural circuits arises from complex maturative processes regulated by poorly understood signaling events, often guided by the extracellular matrix (ECM). Here we report that nanostructured zirconia surfaces, produced by supersonic cluster beam deposition of zirconia nanoparticles and characterized by ECM-like nanotopographical features, can direct the maturation of neural networks. Hippocampal neurons cultured on such cluster-assembled surfaces displayed enhanced differentiation paralleled by functional changes. The latter was demonstrated by single-cell electrophysiology showing earlier action potential generation and increased spontaneous postsynaptic currents compared to the neurons grown on the featureless unnaturally flat standard control surfaces. Label-free shotgun proteomics broadly confirmed the functional changes and suggests furthermore a vast impact of the neuron/nanotopography interaction on mechanotransductive machinery components, known to control physiological in vivo ECM-regulated axon guidance and synaptic plasticity. Our results indicate a potential of cluster-assembled zirconia nanotopography exploitable for the creation of efficient neural tissue interfaces and cell culture devices promoting neurogenic events, but also for unveiling mechanotransductive aspects of neuronal development and maturation.